Perlindungan Mutasi Guru dengan Berlakunya Undang-undang No 23 tahun 2014 Pemerintahan Daerah - Kurniawan, Itok Dwi; Al Muchtar, Suwarma (Integralistik, 2019)
Indonesia is a country based on the rule of law, this is in accordance with the mandate of the constitution. Citizens, in this case especially teachers must get protection in order to be able to carry out their rights and obligations comfortably. After the enactment of Law Number 32 Year 2004 to Law Number 23 Year 2014, secondary education became a provincial affair so there were a lot of teacher mutations. To anticipate this, the government issued a Circular Letter of the Minister of Home Affairs Number 120/5935 / SJ dated October 16, 2015 concerning the Acceleration of the Implementation of Affairs Under Act Number 23 of 2014 concerning Regional Government. The aim of this research is to determine the protection of teacher mutations by the enactment of local government laws. Teachers' protection according to this study can be divided into two, namely preventive (cancellation of regulations / Perbup / Perwali) and repressive (lawsuit of the State Administrative Court). Legal protection for teachers can be done preventively and repressively. Preventively, it could be through the governor's authority as a representative of the government to overturn the decision and repressively, the teacher could submit a claim to the State Administrative Court to cancel the letter of its decision. The existence of this law is expected to improve the welfare of teachers throughout Indonesia.Negara Indonesia adalah negara yang berdasarkan pada aturan hukum, hal ini sesuai dengan amanah konstitusi. Warga negara, dalam hal ini khususnya guru harus mendapatkan perlindungan agar bisa menjalankan hak dan kewajibannya dengan nyaman. Setelah berlakunya UU Nomor 32 Tahun 2004 ke UU Nomor 23 Tahun 2014, pendidikan menengah menjadi urusan provinsi sehingga banyak sekali terjadi mutasi guru. Untuk mengantisipasi hal tersebut, pemerintah mengeluarkan Surat Edaran Menteri Dalam Negeri Nomor 120/5935/SJ tanggal 16 Oktober 2015 tentang Percepatan Pelaksanaan Pengalihan Urusan Berdasarkan Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah. Tujuan peneitian ini adalah untuk mengetahui perlindungan mutasi guru dengan berlakunya undang-undang pemerintah daerah. Perlindungan bagi guru menurut penelitian ini dibedakan menjadi dua, yaitu preventif (pembatalan perda/perbup/perwali) dan represif (gugatan Pengadilan Tata Usaha Negara). Perlindungan hukum terhadap guru bisa dilakukan secara preventif dan represif. Secara preventif, bisa melalui kewenangan gubernur sebagai wakil pemerintah untuk membatalkan keputusan tersebut dan secara represif, guru bisa mengajukan tuntutan kepada pengadilan Tata Usaha Negara untuk membatalkan surat keputusan mutasinya. Dengan adanya undang-undang tersebut diharapkan dapat meningkatkan kesejahteraan para guru di seluruh Indonesia.